Scienza e opinione pubblica Una relazione da ridefinire - Guatelli, Fulvio (Studi e saggi, 2005)
Let's try to imagine a world where scientific illiteracy is the exception rather than the rule. That is a world of subjects who are, in the vast majority, informed and aware of the main ongoing scientific debates, and who are capable of critically and independently thinking about them. A world in which everyone could dispose of the resources to develop a thoughtful opinion on cloning techniques, genetically modified organisms, new anti-cancer therapies or even on the origin of life on Earth and the final destiny of the universe. If this world were possible, what would it look like? The scepticism about the feasibility of such a scenario is justified, however it is equally undeniable that during the twentieth century there have been such profound transformations in the relationship between science and public opinion as to make the question at least legitimate and worthy of an answer.